Color improves “visual” acuity via sound - Levy-Tzedek, Shelly; Riemer, Dar; Amedi, Amir (Frontiers in Neuroscience, 2014)
Visual-to-auditory sensory substitution devices (SSDs) convey visual information via sound, with the primary goal of making visual information accessible to blind and visually impaired individuals. We developed the EyeMusic SSD, which transforms shape, location and color information into musical notes. We tested the 'visual' acuity of 23 individuals (13 blind and 10 blindfolded sighted) on the Snellen tumbling-E test, with the EyeMusic. Participants were asked to determine the orientation of the letter ‘E’. The test was repeated twice: in one test, the letter ‘E’ was drawn with a single color (white), and in the other test, with two colors (red and white). In the latter case, the vertical line in the letter, when upright, was drawn in red, with the three horizontal lines drawn in white. We found no significant differences in performance between the blind and the sighted groups. We found a significant effect of the added color on the ‘visual’ acuity. The highest acuity participants reached in the monochromatic test was 20/800, whereas with the added color, acuity doubled to 20/400. We conclude that color improves 'visual' acuity via sound.